Miles to go : the second journal of The walk - Evans, Richard Paul. (New York : Simon & Schuster, 2011)
Alan Christoffersen, a once-successful advertising executive, wakes one morning to find himself injured, alone, and confined to a hospital bed in Spokane, Washington. Sixteen days earlier, reeling from the sudden loss of his wife, his home, and his business, Alan left everything he knew behind and set off on an extraordinary cross-country journey. Carrying only a backpack, he planned to walk to Key West, the farthest destination on his map. But a vicious roadside stabbing has interrupted Alans trek and robbed him of his one source of solace: the ability to walk. Homeless and facing months of difficult recovery, Alan has nowhere to turnuntil a mysterious woman enters his life and invites him into her home. Generous and kind, Angel seems almost too good to be true, but all is not as it appears. Alan soon realizes that before he can return to his own journey, he must first help Angel with hers.
Keywords: Executives -- Fiction; Life change events -- Fiction; Walking -- United States -- Fiction; Identity (Psychology) -- Fiction; Voyages and travels -- Fiction; Diaries -- Fiction